Human health risks from wastewater-irrigated vegetable farming - Drechsel, Pay; Keraita, Bernard N.; Seidu, R.; Abaidoo, Robert C. (2014)
Contamination levels of water and crops which exceed common standards are only a first indication of human health risks. This chapter shows estimates of human health risks from consumption of wastewater-irrigated vegetables based for example on dose-response modeling. The chapter focuses on human health risks and risk perceptions of microbiological and chemical contaminants such as heavy metals and pesticides.